Performance Evaluation, Measurement and Characterization of Complex Systems Second TPC Technology Conference, TPCTC 2010, Singapore, September 13-17, 2010. Revised Selected Papers - Nambiar, Raghunath; Poess, Meikel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the Second Technology Conference on Performance Evaluation and Benchmarking, TPCTC 2010, held in conjunction with the 36th International Conference on Very Large Data Bases, VLDB 2010, in Singapore, September 13-17, 2010. The 14 full papers and two keynote papers were carefully selected and reviewed from numerous submissions. This book considers issues such as appliance; business intelligence; cloud computing; complex event processing; database optimizations; data compression; energy and space efficiency, green computing; hardware innovations; high speed data generation; hybrid workloads; very large memory systems; and virtualization.
Keywords: Computer science; Computer Communication Networks; Computer system performance; Software engineering; Computer software; Information storage and retrieval systems; Information systems; Computer Science; System Performance and Evaluation; Computer Communication Networks; Information Systems Applications (incl.Internet).; Software Engineering; Algorithm Analysis and Problem Complexity; Information Storage and Retrieval